Development of Strength and Yield Criteria Based on the Relationship between Elastic and Plastic Strains - Li, Y. (Проблемы прочности, 2014)
The presented research results imply a certain relationship between elastic and plastic parts of strain. Based on the preliminary summary of this relationship, a new strength criterion is proposed, which can be treated as modification of the maximum principal strain criterion. Since the proposed approach establishes a relationship between strength and yield criteria, it can also be treated as a new yield criterion. Представлены результаты исследования соотношений между упругими и пластическими деформациями. На основании результатов анализа этих соотношений предложен критерий прочности, который является модификацией критерия максимальных главных деформаций. Поскольку предложенный подход увязывает критерии прочности и пластического течения, данный критерий можно трактовать как новый критерий пластического течения. Представлено результати дослідження співвідношень між пружними і пластичними деформаціями. На основі результатів аналізу цих співвідношень запропоновано новий критерій міцності, який є модифікацією критерію максимальних головних деформацій. Оскільки запропонований підхід ув'язує критерії міцності і пластичної плинності, даний критерій можна трактувати як новий критерій пластичної плинності.